2015
DOI: 10.1007/s10096-015-2478-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of preoperative skin antisepsis and clonal relationship to postantiseptic skin-and-wound flora in patients undergoing clean orthopedic surgery

Abstract: Nosocomial surgical site infections (SSI) are still important complications in surgery. The underlying mechanisms are not fully understood. The aim of this study was to elucidate the possible role of skin flora surviving preoperative antisepsis as a possible cause of SSI. We conducted a two-phase prospective clinical trial in patients undergoing clean orthopedic surgery at a university trauma center in northern Germany. Quantitative swab samples were taken from pre- and postantiseptic skin and, additionally, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…This is consistent with ndings from an earlier study in which CNS were frequently detected in the surgical eld after 3 minutes of preoperative skin antisepsis with CHG-ALC (unpublished ndings). This is also consistent with data from another study [4] that showed growth of residual bacteria directly after skin antisepsis with 70% v/v isopropanol in 35% of operations in orthopedic surgery. Among the isolates recovered after antisepsis, 53% were identi ed as CNS, and clonally related strains were subsequently found in surgical wounds in 10% of operations [4].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with ndings from an earlier study in which CNS were frequently detected in the surgical eld after 3 minutes of preoperative skin antisepsis with CHG-ALC (unpublished ndings). This is also consistent with data from another study [4] that showed growth of residual bacteria directly after skin antisepsis with 70% v/v isopropanol in 35% of operations in orthopedic surgery. Among the isolates recovered after antisepsis, 53% were identi ed as CNS, and clonally related strains were subsequently found in surgical wounds in 10% of operations [4].…”
Section: Discussionsupporting
confidence: 92%
“…This is also consistent with data from another study [4] that showed growth of residual bacteria directly after skin antisepsis with 70% v/v isopropanol in 35% of operations in orthopedic surgery. Among the isolates recovered after antisepsis, 53% were identi ed as CNS, and clonally related strains were subsequently found in surgical wounds in 10% of operations [4]. These data underscore the need for better protection against CNS in surgery by potent antisepsis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In aerobic cultures, PVP-I-ALC was better than CHG-ALC only after 2.5 min contact time and immediate sampling ( Table 2), but not in any other of the tested parameters, including prolonged application time and sampling after 3 h. CNS which multiplies aerobically and to a lesser extend anaerobically, were not completely eliminated by CHG-ALC. This corresponds with findings that after 3 minutes of preoperative skin antisepsis with CHG-Alc always CNS were detected in smears in the surgical field before implantation of hip endoprostheses (unpublished) and also with data showing bacterial growth directly after skin antisepsis (propan-2-ol (70 % v/v) in 35% of operations in traumatology, whereof 53% were identified as CNS which finally caused wound contaminations in 10% of operations with clonally related strains [4]. These data underline the need for better protection against CNS in at least orthopaedic and trauma surgery by adequate potent antisepsis in order to better prevent up to now still unacceptable infection rates predominantly caused by CNS.…”
Section: Discussionsupporting
confidence: 90%
“…The skin flora of patients is one of the most important factors in the pathogenesis of surgical site infections (SSI) [1][2][3][4]. Skin antisepsis constitutes an effective measure to reduce the numbers of microorganisms on skin and has been included as a key measure to prevent SSIs in recent international guidelines and recommendations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%